2016
DOI: 10.1016/j.eururo.2016.02.058
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Inflammatory Mediators in Bladder Pain Syndrome

Abstract: BackgroundBladder pain syndrome (BPS) pathology is poorly understood. Treatment strategies are empirical, with limited efficacy, and affected patients have diminished quality of life.ObjectiveWe examined the hypothesis that inflammatory mediators within the bladder contribute to BPS pathology.Design, setting, and participantsFifteen women with BPS and 15 women with stress urinary incontinence without bladder pain were recruited from Cork University Maternity Hospital from October 2011 to October 2012. During c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…The stainings show the effect of the two secondary antibodies used, Alexa 488 donkey antimouse, and donkey antirabbit in A and B, respectively, with the omission of the primary antibodies animal models have established that it contributes to the barrier function. 5,8,9,11 An in vitro study by Janssen et al 8 showed that specific removal of CS with the enzyme chondroitinase significantly reduced barrier function as measured by TEER. One main treatment strategy in BPS/ IC aims at recovery of the barrier function through exogenous GAG-replenishment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The stainings show the effect of the two secondary antibodies used, Alexa 488 donkey antimouse, and donkey antirabbit in A and B, respectively, with the omission of the primary antibodies animal models have established that it contributes to the barrier function. 5,8,9,11 An in vitro study by Janssen et al 8 showed that specific removal of CS with the enzyme chondroitinase significantly reduced barrier function as measured by TEER. One main treatment strategy in BPS/ IC aims at recovery of the barrier function through exogenous GAG-replenishment.…”
Section: Discussionmentioning
confidence: 99%
“…8 These results were later confirmed in vivo in a mouse and a rat model. [10][11][12] Offiah demonstrated that removing the urothelial GAGs in the rat bladder induces comparable symptoms as seen in BPS/IC patients such as inflammation, pain, and increased excitability of the urinary bladder. 11 In BPS/IC patients, intravesical GAGreplenishment therapy is frequently applied to restore the GAG layer, improve the urothelial barrier and thus relieve complaints.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Gene expression studies have uniformly indicated over-expression of pro-inflammatory cytokines and ligands or cellular receptors to noxious stimuli. [9][10][11][12][13][14][15] Further studies demonstrate B-cell dominant lymphocytic infiltration and activation of the infiltrating B-cells. Furthermore, light-chain restriction, index of the clonal Y HOMMA expansion of B-cells, is frequently observed in the infiltrating B-cells of HIC bladder.…”
Section: Significance Of Hunner Lesionsmentioning
confidence: 91%
“…In other words, HIC is pan‐cystitis associated with epithelial denudation. Gene expression studies have uniformly indicated over‐expression of pro‐inflammatory cytokines and ligands or cellular receptors to noxious stimuli . Further studies demonstrate B‐cell dominant lymphocytic infiltration and activation of the infiltrating B‐cells.…”
Section: Rationale For Sub‐categoriesmentioning
confidence: 99%